Investigation of Monotonic and Cyclic Behavior of Soft Clay Using Direct Simple Shear Apparatus - BENCHANUKROM, Sutera; LAILAK, Chitsirin; KONKONG, Nirut (Engineering Transactions, 2019)
The purpose of this research was to study the monotonic and cyclic simple shear mode behavior of Bangkok clay, using direct simple shear apparatus. The monotonic specimens were prepared in a saturated condition and were K0 consolidated before being undrained sheared. The specimens were sheared at the shear strain rate of 5% per hour until the shear strain reached 20%. The Stress History and Normalized Soil Engineering Properties (SHANSEP) method was applied to analyze the monotonic test data, and the CK0DSS SHANSEP equation was proposed, based on the results. The results from the CK0DSS SHANSEP equation were in a good correlation with Qu, CK0CU and CK0EU. The cyclic specimens were tested at different frequencies of 0.1, 1 and 5 Hz and the vertical stress was varied at 200, 300, and 400 kPa. The shear strain amplitude was controlled at ±0.5% for the first 100 cycles, and then was increased to ±1.5% for the next 100 cycles, and finally it was increased to ±3% for the last 100 cycles. The results showed that the shear modulus increased when the maximum vertical effective stress increased and the damping ratio increased when the strain amplitude increased.